2015
DOI: 10.1007/s12272-015-0648-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of inflammation in Alzheimer’s disease pathogenesis and therapeutic potential of anti-inflammatory agents

Abstract: Alzheimer's disease (AD) is the most common form of dementia. It is characterized by beta-amyloid (Aβ) peptide fibrils, which are extracellular depositions of a specific protein, and is accompanied by extensive neuroinflammation. Various studies have demonstrated risk factors that can affect AD pathogenesis, and they include accumulation of Aβ, hyperphosphorylation of tau protein, and neuroinflammation. Among these detrimental factors, neuroinflammation has been highlighted by epidemiologic studies suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 159 publications
(155 reference statements)
2
70
0
Order By: Relevance
“…Experimental and clinical findings provide evidence for the hypothesis that the neuronal degeneration in AD is not simply due to the Aβ deposition, but to neuroinflammation [45,46]. Consistent with the above studies, an increased expression of TNF-α gene was found in the present AD cellular model.…”
Section: Discussionsupporting
confidence: 87%
“…Experimental and clinical findings provide evidence for the hypothesis that the neuronal degeneration in AD is not simply due to the Aβ deposition, but to neuroinflammation [45,46]. Consistent with the above studies, an increased expression of TNF-α gene was found in the present AD cellular model.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, there is an ever-expanding pool of data from both human studies and animal models of AD that highlights the crucial role played by neuroinflammation in AD. For recent reviews of the literature in this field, the reader is directed to the following comprehensive articles (Heneka et al, 2015;Heppner et al, 2015;McGeer and McGeer, 2013;Shadfar et al, 2015). Epidemiological and clinical studies in human AD patients have provided some interesting perspectives on neuroinflammation and in some cases have stimulated further work in animal models of the disease.…”
Section: Neuroinflammation In Admentioning
confidence: 99%
“…[36][37][38] On the other hand, the microglia had been shown to play an important role in synaptic formation and plasticity during brain development. 47,48 We found increased microglia accumulation and expression of inflammatory cytokines in the cortex or the hippocampus in 5XFAD mice compared with WT mice, while BHBA treatment significantly attenuated neuro-inflammation. 41,42 Furthermore, activated microglia express pro-inflammatory enzymes (iNOS and COX-2) and cytokines (TNF-α, IL-1β, and IL-6), 43 which may mediate neuronal degeneration, 44,45 Using mass spectrometry with bioinformatic analysis, Antonio et al found activation of JAK/STAT, p38 MAPK, and interleukin pathways in microglial cells of 5XFAD mice, indicating that innate immune alterations are elicited in microglial cells before plaque deposition in the AD mouse model.…”
Section: Discussionmentioning
confidence: 81%